The Conservation Of Green Sea Turtles (Cheloniidae: Chelonia Mydas) At Setiu, Terengganu, Malaysia - Mutalib, Aini Hasanah Abd (2014)
This study conservation of green sea turtles (Chelonia mydas) at Setiu was studied by determining their distribution, nest characteristics, clutch size, nesting morphology of the nesting green turtles, false crawl attempts, successful nesting attempts and emergence hour. Hatchery management was also facilitated by measuring the successive hatching rate, duration of incubation, egg condition, hatchlings’ growth and hatchlings’ carapacial scutes variation. This study also assessed socio-demographic aspect on the trends of consuming turtle eggs. Secondary data on nesting ecology and behaviour were collected from 2007 to 2012. Data on successful hatching rate and days of incubation were collected from 2009 to 2012. Hatchlings’ growth and carapacial scute variation were determined in the year 2012. Survey forms were collected from the communities in Setiu to assess their level of awareness regarding green sea turtle conservation. Telaga Papan has significantly the highest distribution of green marine turtle nesting than the other five beaches (ANOVA, F 5, 42 = 8.87, p< 0.0001). The highest number of successful nesting attempts was in 2012 (mean = 28.71 ± 6.58). There was no correlation between size of the female turtles and the number of eggs (rs = 0.23, p = 0.14). The majority of the turtles landed between 1200h and 0159h (23%). There was a strong correlation between successful nesting attempts with false crawls (rs= 0.88, p= 0.02). Results show that there was a significant difference in successive hatching rate between the years (F3, 618 = 5.05, P = 0.002). There was no significant difference for successive hatching rates among the beaches over the four years (F4, 618= 1.06, P = 0.39).